“The impact of using the of the Government Finance Statistics Manual (GFSM) on The General Budget in Iraq” - محمد, صفاء احمد; كامل, رؤى مصطفى (Journal of Economics and Administrative Sciences, 2018)
This research is aiming  to analyze the impacts of the current budget in Iraq by using  the Government Finance Statistics Manual (GFSM) , the research is based on hypothesis: (There is an impact on the using of the Government Finance Statistics Manual (GFSM) In public budget in Iraq) .This hypothesis was demonstrated by using the questionnaire, a number of conclusions were reached, the most important being the lack of terminology adopted in the government accounting system and the Iraqi financial and accounting manual as a result of their adoption of the monetary basis for the lack of accounting terminology that meets the requirements of (GFSM) on an accrual basis the adoption of GFSM contributes to the development of accounting principles and policies and helps to provide a lot of information that meets the requirements of financial management in general and government accounting systems in particular for the management and optimal utilization of government resources, one of the most important recommendations is to adapt the Iraqi government accounting system and the current financial and accounting manual with (GFSM) in line with the requirements of the economic and political environment in Iraq to work on the adoption of (GFSM) in terms of the accounting principles, procedures and accounting policies adopted by it, taking into account the specific circumstances of the Iraqi environment, and working towards the adoption of the budget of programs and performance instead of the current traditional budget and provide information on the state programs and results of its activities and the transition to planning the general budget in the medium term to provide an opportunity to comply with the basis of accrual accounting, as well as the development of the government accounting guide currently supported with (GFSM) encodings and patches.